Investigation of the Relationship Between Anxiety Levels of Patients Before Plastic Surgery Operation and Worship Practices in Muslims - Muslu, Ümran (Journal of religion and health, 2020)
There is an increasing interest in the effects of preoperative anxiety on the course and outcomes of surgical treatments and also in the studies about the anxiety-decreasing interventions. The present study aims to identify the relationship between the preoperative anxiety level of the individuals prior to aesthetic surgery operations such as nose, ear, eyelid, and mammoplasty and religious rituals such as performing prayers, fasting, and going to pilgrimage. The frequency of performing the religious rituals was identified through a questionnaire. The questionnaire included questions about the religious rituals such as performing prayers, going to a pilgrimage, and fasting as well as questions about sociodemographic features such as gender, age, and education level of the patients. Preoperative anxiety level was measured using the "Anxiety Specific to Surgery Questionnaire." The nonparametric Mann-Whitney U test was used for the scale score comparisons of the two independent groups. The scale score comparisons of more than two groups were performed using the Kruskal-Wallis test. The relationships between age and scale scores were analyzed using the Spearman's correlation coefficient. The study involved 117 patients who were planned to undergo an aesthetic surgery operation. The scale scores were significantly different according to the pilgrimage groups (p?=?0.004). The scale scores were significantly different according to the level of fasting (p?=?0.022). No significant differences were found between the scales scores of the groups who reported the frequency of performing prayer as never, sometimes or five times (p?=?0.515). In conclusion, the present study found that Muslim people who performed religious rituals more often experienced less preoperative anxiety levels in plastic surgeries, which indicates that the belief level is an effective factor in preoperative anxiety levels. The findings of the present study indicate that patients' beliefs and worship practices should be taken into consideration by doctors, operating room personnel, and even all health workers in order to decrease the anxiety levels of patients who will undergo surgery.